Refocusing Physics Education in Nigeria: Issues and Challenges in Teacher Education - Udoh, Okon Akpakpan (Richtmann Publishing, 2012)
This paper spotlights a number of daunting challenges that fraught teachers education in Nigeria. Itadjudges senior secondary education as being stuck in limbo, using senior secondary physics as illustratedexamples. It advocates a repositioning of basic elements of teacher education inline with the realities of the21st century.